Analisis Kompetensi Technological Pedagogical Content Knownledge (TPACK) dan CoRes (Content Representation) pada Materi Genetika - Arif, Sunarto; Syahirah, St.; Hartini, Venty Sugih; Rahmat, Adi; Riandi (Pedagogi Hayati, 2024)
ABSTRACT. Education plays a critical role in developing the potential of each individual, and the quality of the teaching and learning process is vital for the success of the education undertaken by students. Innovative learning designs that meet student needs are required. Genetic material in biology, which is complex and conceptual, requires deep understanding. Therefore, it is important for educators to use teaching strategies that allow students to better understand genetic concepts. The purpose of this study is to evaluate genetic teaching strategies including curriculum analysis, approaches, and the application of various models, methods, and media in learning. This research method is qualitative with a descriptive approach, aiming to describe current genetic teaching practices, including the use of TPACK by teachers. Data was collected through literature study with stages such as data collection, organization, analysis, interpretation, and conclusion with descriptive qualitative data analysis. The analysis results were verified by experts. The findings show that teachers have implemented various approaches, models, methods, and learning media. The success of the learning process greatly depends on effective teacher planning so that students can clearly understand the material. These findings provide useful information for teachers to implement TPACK in genetics learning. Keywords: TPACK, Content Representation, Genetic ABSTRAK. Pendidikan memiliki peran yang sangat penting dalam mengembangkan potensi setiap individu, dan kualitas proses belajar mengajar sangat menentukan keberhasilan pendidikan yang dijalani Peserta Didik. Diperlukan desain pembelajaran yang inovatif dan sesuai dengan kebutuhan Peserta Didik. Materi genetika dalam biologi, yang bersifat kompleks dan konseptual, membutuhkan pemahaman yang mendalam. Oleh karena itu, penting bagi pendidik untuk menggunakan strategi pembelajaran yang memungkinkan siswa memahami konsep genetika dengan lebih baik. Tujuan dari studi ini adalah untuk mengevaluasi strategi pengajaran genetika yang mencakup analisis kurikulum, pendekatan, serta penerapan berbagai model, metode, dan media dalam pembelajaran. Metode penelitian ini bersifat kualitatif dengan pendekatan deskriptif, dan bertujuan untuk menggambarkan praktik pengajaran genetika saat ini, termasuk penggunaan TPACK oleh guru. Data dikumpulkan melalui studi literatur dengan tahapan seperti pengumpulan data, pengorganisasian, analisis, interpretasi, dan kesimpulan dengan analisis data secara kualitatif deskriptif. Hasil analisis diverifikasi oleh tenaga ahli. Hasil menunjukkan bahwa guru sudah menerapkan berbagi pendekatan, model, metode dan media pembelajaran. Kesuksesan proses belajar sangat bergantung pada perencanaan guru yang efektif sehingga siswa dapat memahami materi dengan jelas. Temuan ini memberi informasi yang berguna bagi guru untuk mengimplementasikan TPACK dalam pembelajaran genetika. Kata Kunci: TPACK, Content Representation, Genetika